What Works in Improving Gender Equality International Best Practice in Childcare and Long-term Care Policy - Rummery, Kirstein (Policy Press, 2021)
EPDF and EPUB available Open Access under CC-BY-NC licence. This book provides an accessible analysis of what gender equality means and how we can adapt best practice in care policies from other countries. It provides realistic feasible policy solutions, the role of individuals, families, communities, the market and the state, and the difficulties in different policy contexts.